Aberrant X chromosome dosage compensation causes hybrid male inviability in Caenorhabditis - Yongbin Li; Yimeng Gao; Jiaonv Ma; Yifan Gao; Jiemei Tang; Rui Yang; Jiajia Wang; Wangyan Zhou; Hantang Zhang; Wenhua Shao; Zhijin Liu; Zhongying Zhao; et al. (Proceedings of the National Academy of Sciences, 2025)
Zygotic reproductive isolation frequently initiates with hybrid incompatibility in the heterogametic sex, such as males in XX/XY systems. The genetic basis of hybrid male incompatibility has long remained elusive. Here, we show that crosses of Caenorhabditis nigoni males with C. briggsae females result in insufficient expression of Cbr-xol-1 , an X-linked master switch responsible for intimately linked sex determination and dosage compensation pathways, consequently triggering aberrant X-chromosome repression in males, and ultimately leading to embryonic inviability. In contrast, male embryos from the reciprocal cross maintain normal expression level of C. nigoni xol-1 genes, consistent with their viability. We further demonstrate that the cis-regulatory regions of Cbr-xol-1 and Cni-xol-1 have functionally diverged. Finally, X transcription is also aberrantly repressed in lethal hybrid male embryos from crosses between gonochoristic species C. latens and C. remanei . Our results suggest an evolutionary scenario in which incompatibility of the dosage compensation system leads to reproductive isolation.